The relative contribution of athletes' mental skills to some integrated attacking skills among junior football players - Yaseen, Abdul Razzaq Waheeb; Darweesh, Yousif Abdul Ameer; Wadi, Hiba Hameed (International Journal of Psychosocial Rehabilitation, 2020)
This study addressed the importance of mental skills in the field of sports and its association with theperformance of players, especially junior football players with focus on their attacking skills. The problem of this study was that most coaches do not pay attention to the psychological aspect and mental skills of junior players, but focus only on the physical and skill aspects in their training units. Therefore, the importance of research lies in identifying the contribution of mental skills to the integrated attacking skills so that the coach and psychologist can develop the appropriate mental strategies to improve the attacking skills and predict their level among their players. In this study, the descriptive method of correlation was employed to analyze research data. The research sample consisted of (72) junior players. The Ottawa mental skills assessment tool (henceforth, OMSAT-3) was applied to determine the relationship between mental skills and some integrated attacking tests. The study concluded that there is a negative correlation between the variables of OMSAT-3 and some integrated attacking skills among junior football players at the level of (0.01) and (0.05). In addition, equations were formed to predict the time of integrated attacking tests in relation to some variables of OMSAT-3.